GABAA Receptor Subunit Transcriptional Regulation, Expression Organization, and Mediated Calmodulin Signaling in Prefrontal Cortex of Rats Showing Testosterone-Mediated Impulsive Behavior - Agrawal, Juhee; Dwivedi, Yogesh (Frontiers in Neuroscience, 2020)
Testosterone can induce impulsivity, a behavioral impairment associated with various psychiatric illnesses. The molecular mechanisms associated with testosterone-induced impulsivity are unclear. Our earlier studies showed that supraphysiological doses of testosterone to rats induced impulsive behavior, impacted hypothalamic-pituitary-adrenal axis and hypothalamic-pituitary-gonadal axis interactions, and altered α2A adrenergic receptors in prefrontal cortex (PFC). Owing to the importance of GABAergic system in impulsivity and memory, the present study examines whether testosterone-mediated impulsivity is associated with changes in the expression of Gamma-Aminobutyric Acid (GABA) A and B receptor subunit transcripts (Gabra1, Gabra2, Gabra2 transcript variant 2, Gabra3, Gabra4, Gabra5, Gabra6, Gabrb1, Gabrb2, Gabrb3, Gabrg1, Gabrg2, Gabrg3, Gabbr1, Gabbr2) in rat PFC, and whether testosterone influences GABAA receptor subunit organization. We studied GABA receptor functions by examining GABA receptor-mediated calcium/calmodulin-dependent kinase signaling genes (Calm1, Calm2, Calm3, Camk2a, Camk2b, Camk2g, Camk2d, Camk4) in the testosterone-induced impulsivity model. Rats were left untreated as controls (C), gonadectomized (GDX), or GDX and injected with supraphysiological doses of testosterone (T). Impulsive behavior was examined using the go/no-go paradigm. Gene expression was studied using qRT-PCR and GABAA subunit reorganization using cross correlation. Our findings show that expressions of select GABAA receptor subunits (Gabra3, Gabra5, Gabra6) were significantly upregulated in PFC of T group compared to GDX or C groups. GABAA receptor subunit organization was different in C, T, and GDX groups. Additionally, Camk4 expression was significantly downregulated in T compared to C group. Our findings suggest that specific GABAA receptor subunit expression, their reorganization, and Camk4-mediated functions may be associated with testosterone-mediated impulsivity.